2018
DOI: 10.1016/j.ejpb.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the in vitro and in vivo performance of oral cocrystal formulations via spray coating

Abstract: Engineering of pharmaceutical cocrystals is an advantageous alternative to salt formation for improving the aqueous solubility of hydrophobic drugs. Although, spray drying is a well-established scale-up technique in the production of cocrystals, several issues can arise such as sublimation or stickiness due to low glass transition temperatures of some organic molecules, making the process very challenging. Even though, fluidised bed spray coating has been successfully employed in the production of amorphous dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…The sample mass was allowed to reach equilibrium, defined as dm/dt ≤ 0.002 mg/min over 10 min, before the RH was changed [30].…”
Section: Dynamic Vapour Sorption (Dvs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The sample mass was allowed to reach equilibrium, defined as dm/dt ≤ 0.002 mg/min over 10 min, before the RH was changed [30].…”
Section: Dynamic Vapour Sorption (Dvs)mentioning
confidence: 99%
“…where k is the degradation rate (% remaining drug/day), T is the temperature in Kelvin degrees, a is the collision factor, B is the humidity factor, RH is the relative humidity, Ea is the activation energy in kcal mol −1 , and R is the gas constant (0.00198 kcal K −1 mol −1 ) [30]. In order to calculate the degradation rate, the amount degraded at different time points was fitted at each condition to the following kinetic models: zero-order, first-order, second order, Avrami and diffusion using the following equations (Equations (12)-(16)) [39]:…”
Section: Accelerated Stability Studiesmentioning
confidence: 99%
“…In general, a multicomponent crystal phase includes a salt, cocrystal, hydrate, and solvate [32,33]. Numerous studies have demonstrated that the formation of a multicomponent crystal phase of API with a suitable excipient could enhance its physicochemical properties, such as solubility and dissolution rate, permeability, bioavailability, physical stability, compressibility, and pharmacological efficacy [34][35][36][37][38][39]. To the best of our knowledge, only two studies on the multicomponent crystal phase of piperine have been reported: a cocrystal with resveratrol, and a salt with a halide [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of the cocrystalline phase of ibuprofen with certain coformers has improved the drug’s solubility, intrinsic dissolution rate, and overall performance. The drug shows no likelihood to agglomerate in aqueous media, and can improve its chemical stability [ 7 ]. In addition, the mechanical properties and hygroscopicity of the compound are also reported to have improved simultaneously.…”
Section: Introductionmentioning
confidence: 99%